Portable transcutaneous electrical nerve stimulation therapy at different frequencies in the treatment of knee osteoarthritis: a quasi-experimental study - Charles, Ang Poh Thean; Awang, Mohd Shukrimi; Zakaria@Mohamad, Zamzuri; Abdul Razak, Ardilla Hanim (Aegis of Indian Orthopaedic Research Group (IORG), 2020)
Introduction: The prevalence of knee osteoarthritis is on the raise. This raise has been a huge financial burden to developed countries in treating the disease. Transcutaneous electrical nerve stimulation (TENS) is a cost-effective, easily available, and self-applicable mode of nonpharmacological pain relieve technique. Despite these advantages, the use, settings, and effectiveness of portable TENS are still poorly understood. The aim of this study is to determine the effectiveness of portable TENS at different frequencies in treating knee osteoarthritis. Materials and Methods: This is a single-center quasi-experimental study involving 100 patients seen in the outpatient department with knee osteoarthritis. They were randomly (computer generated) allocated into two arms (high frequency [H-F] or low frequency [L-F]). H-F is set at 100 Hz and L-F is set at 4 Hz. A baseline assessment is taken with the visual analog score (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Oxford Knee Score, and Lequesne index. They were instructed to self-administer the TENS therapy as per protocol and followed up at the 4th and 12th week to be reevaluated on the above scores. Results: The final results show that both H-F and L-F groups showed improvement in all parameters of the VAS, WOMAC index, Oxford Knee Score, and Lequesne index (73%). Only the pain component of Lequesne index, activities of daily living component of Lequesne index, total Lequesne index, and pain component of WOMAC index shows a statistically significant difference, favoring the H-F group. The H-F group yields a faster result; however, with time the overall effect remains the same in both groups.